Bronchial thermoplasty as a treatment for severe asthma: controversies, progress and uncertainties. (3rd April 2018) - Thomson, Neil C
ABSTRACT: Introduction : Bronchial thermoplasty is a licensed non-pharmacological treatment for severe asthma. Area covered : This article considers evidence for the efficacy and safety of bronchial thermoplasty from clinical trials and observational studies in clinical practice. Its place in the management of severe asthma, predictors of response and mechanisms of action are reviewed. Expert commentary : Bronchial thermoplasty improves quality of life and reduces exacerbations in moderate to severe asthma. Morbidity from asthma is increased during treatment. Overall, patients treated in clinical practice have worse baseline characteristics and comparable clinical outcomes to trial data. Follow-up studies provide reassurance on long-term safety. Despite some progress, future research needs to investigate uncertainties about predictors of response, mechanism of action and place in management of asthma.